A feasibility study on Sessy liquor-laced ice cream - Alberto, Nina Desiree May G.; Bravo, Kristine Joy R.; Gerna, Cecille S.; Pelle, Stephanie (College of Engineering, University of the Philippines Diliman, 2010)
Sessy is a liquor-laced ice cream bar that offers a great experience of bonding and indulgence with the unique combination of liquor and ice cream in just one scoop. The ice cream bar to be located in Alabang is first of its kind and a destination spot that offers different variations of 12 liquor-laced ice cream flavors with add-ons like crepe and brownie. With the store seating capacity of 24, the in-store production facility produces the exquisite blend of liquor-laced ice cream with only 5% alcohol content which is made to appeal to the emotions and hearts of female customers. The business targets female college students and young professionals from A, B and C who wants to be rewarded or relax after a whole day of work and study. Indeed, this defined target market is somehow new to the fairly saturated ice cream industry as the main players are observed to always include families and children as their target. However, the exceptional concept of an adult-oriented ice cream in the market puts the company in a competitive position as it pioneers the introduction of liquor-laced ice cream in a bar. It redefines an existing market for the market industry and is consistent with the trend in the behavior of the target market which is their willingness to try and patronize new products and gadgets in the market. In line with this, marketing efforts will be focused on print advertisements in the popular female-oriented magazines and in the network sites. The existing competitor Lickquer Adult Ice Cream has acquired media publicity about their product liquor-laced ice cream. Since the competitor offers their product for delivery and pick-up only, Sessy takes advantage of the awareness of the public about the product and matches it with the ambiance and feel that suits the taste of the target. Based on the size of our market and survey of the target market, the company's sales projections for the first year are P4,500,000. The break-even sales volume is 2,289 liters on the first year which can be attained by the marketing plan of the company and the strategic location of the store. Over the five years, ending cash projections are positive. A large percentage of start-up cost is for the buying of equipment for the production facility but the Asset Turnover for the next five years is increasing starting from an acceptable value of 1.67 which projects that the business is effective in using its short-term and long-term assets. Also, the business will operate in its first year with an acceptable return on Equity ratio of 0.33. The management of Sessy consists of the sole operating with eight crews. Extensive experience in restaurant or bar management can help a lot in managing the company. The owner may invest in an amount of Php860,000 as his/her capital in the business. The remaining amount for start-up costs may be loaned from the bank. The owner may choose to shoulder the total start-up cost of Php2,000,000. The business appeals to the niche market which is the trend now in the market. The business is in a good position to be the first to introduce the concept of liquor-laced Ice Cream bar. It is also profitable based on the financial projections over the five years of operation.